Government Agencies
XXII, 474 p.
Keywords: This book describes and compares how semi-autonomous agencies are created and governed by 30 governments. It leads practitioners and researchers through the crowded world of agencies, describing their tasks, autonomy, control and history. Evidence-based lessons and recommendations are formulated to improve agencification policies in post-NPM times.